Efektivitas Exercise-Based Intervention dalam Mengurangi Gejala Gaming Disorder pada Remaja: Studi Kuasi Eksperimental - Ilham, Rausyan Fikri Muhammad; Ikaputri, Nada Khalisha; Iltizamulloh, Muhammad Rafli; Jasmine, Salwa Naira Aluina; Islaha, Shafia (Universitas Trunojoyo Madura, 2025)
Research on gaming disorder and its prevention has been intensified since the World Health Organization (WHO) included gaming disorder in the 11th edition of the International Classification of Diseases (ICD-11). This study aims to examine the effectiveness of exercise-based intervention in reducing symptoms of gaming disorder in adolescents. A quasi-experimental method with an interrupted time-series design was used to compare participants' conditions between before and after the intervention. The sampling method used was purposive sampling with the following criteria: (1) adolescents aged 12-18 years, (2) playing games, (3) getting a score of five or more on The Ten-Item Internet Gaming Disorder (IGDT-10) instrument. Five participants (n = 5) who met the criteria then participated in the intervention procedure for three days. Wilcoxon Signed Ranks Test was used to analyze the significance of the difference in scores between pre- and post-intervention. The results indicated that there was a significant reduction in gaming disorder symptoms between pre- and post-intervention (T = 0.00, p 0.05, n = 5, = 0.00, = 15.00). This research has practical implications for the use of exercise-based intervention to prevent and treat gaming disorder in adolescents and its application in educational and clinical settings. Similar research with the use of objective indicators, the use of randomized sampling techniques, and the provision of interventions over a long period of time is highly recommended to improve the quality of future research.